Monetary Reaction Function in Indonesia During Inflation Targeting Period - Aloysius Deno Hervino; Insukindro Insukindro; Amirullah Setya Hardi; Sekar Utami Setiastuti (Jurnal Ekonomi dan Studi Pembangunan, 2023)
This study analyzes the monetary reaction function with shocks and the fear of floating phenomenon in the inflation targeting period in Indonesia. This study uses a new neoclassical synthesis approach. The unit root test result explains that all variables are stationary or I(0), and the long-run regression model is estimated. The results show that interest rates respond positively to future inflationary (counter-cyclical) in the log-run. The effect of triple shocks on interest rates in Indonesia is estimated using the Forward-Looking Model (FLM) and Error Correction Model (ECM). Using a predictive model performance (informal test), the best model in this study is FLM. In the short-run, only fluctuations in world oil prices significantly affect interest rates (counter-cyclical policy). Furthermore, BI's response to future inflation cannot be compared with BI's response to economic fluctuations, so this study has not been able to explain the significant effect of economic fluctuations on deposit interest rates. It means that the fear of the floating phenomenon cannot be explained in this study.